Auxin Control in the Formation of Adventitious Roots - Tiberia I. POP (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2011)
Adventitious rooting is a complex process and a key step in the vegetative propagation of economically important woody, horticultural and agricultural species, playing an important role in the successful production of elite clones. The formation of adventitious roots is a quantitative genetic trait regulated by both environmental and endogenous factors. Among phytohormones, auxin plays an essential role in regulating roots development and it has been shown to be intimately involved in the process of adventitious rooting. Great progress has been made in elucidating the auxin-induced genes and auxin signaling pathway, especially in auxin response Aux/IAA and Auxin Response Factor gene families. Although some important aspects of adventitious and lateral rooting signaling have been revealed, the intricate signaling network remains poorly understood. This review summarizes some of the current knowledge on the physiological aspects of adventitious root formation and highlights the recent progress made in the identification of putative molecular players involved in the control of adventitious rooting. Despite much has been discovered regarding the effects and regulation of auxins on plant growth since the Darwin experiments, there is much that remains unknown.